Adjusting Fermi Level of Graphene by Controlling the Linker Lengths of Dipolar Molecules - Zhang, Mingjia (Langmuir : the ACS journal of surfaces and colloids, 2019)
Graphene modified by azo molecules has attracted much attention due to its promising graphene-enhanced Raman scattering (GERS) effect. Herein, we achieved the shortened distance between the dipole moment and graphene, by reducing the number of methylene groups and the chain length, and studied the Raman scattering in dipolar molecules/graphene hybrids. Whether for low or high concentrations, a more significant GERS signal can be observed, which can be attributed to the effective modulation of the dipole moment on interface energy level matching. Further, by fabricating FET devices, we demonstrate more obvious p-type and n-type doping in graphene that is affected by the chain length of the azobenzene molecule. On the basis of the dependence of the G band shift on the Fermi surface change, we further reveal the important role of dipole moment distance in dipolar molecules/graphene hybrids. These studies provide a new approach to optimize the interface matching between azobenzene and graphene and may help achieve more sensitive GERS detection